2013
DOI: 10.4236/ajor.2013.33029
|View full text |Cite
|
Sign up to set email alerts
|

An Existence Theorem of Solutions for the System of Generalized Vector Quasi-Variational-Like Inequalities

Abstract: In this paper, we introduce and study the system of generalized vector quasi-variational-like inequalities in Hausdorff topological vector spaces, which include the system of vector quasi-variational-like inequalities, the system of vector variational-like inequalities, the system of vector quasi-variational inequalities, and several other systems as special cases. Moreover, a number of C-diagonal quasiconvexity properties are proposed for set-valued maps, which are natural generalizations of the g-diagonal qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Ameln and Fuglum [21] however concluded that when the transshipment cost is not taken into account the transshipment in the optimal solution will probably be inappropriately large. Husain et al [27]; Gupta et al [28]; Birla et al [29]; Deepmala [30]; Mishra [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ameln and Fuglum [21] however concluded that when the transshipment cost is not taken into account the transshipment in the optimal solution will probably be inappropriately large. Husain et al [27]; Gupta et al [28]; Birla et al [29]; Deepmala [30]; Mishra [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A survey on the linear bi-level programming problem has been written by O. Ben-Ayed [23]. The complexity of the problem has been addressed by a number of authors [24] [25] [26]. It has been proved that even the linear bi-level programming problem [27] [28].…”
Section: Introductionmentioning
confidence: 99%
“…Using decomposition techniques, an algorithm based on benders decomposition to solve the linear mixed integer binary problem, with the method, the target value bounded, are used to transform the problem into problems of one level [25]. Based on the use of benders decomposition with a continuous sub problems [26,30].…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the problem has been addressed by a number of authors [16] [17] [18]. It has been proved that even the linear bi-level programming problem where all the involved functions are affine, is a strongly NP-hard problem [19] [20].…”
Section: Introductionmentioning
confidence: 99%